‘As a person you need help every now and then’: Accessing Students’ Support Needs in a Higher Education Environment - Manik, Sadhana (South African Journal of Higher Education, 2016)
Student departure from HEIs in SA has recently garnered renewed enthusiasm with attempts by researchers to understand and address its impact on university statistics. Whilst studies initially focused on the aetiology of student departure, the pendulum has now started to swing in the direction of the elements and environments for students achieving success in higher education. A key perspective involves gaining insight into what students need to achieve success. This article reports on undergraduate students’ conceptions of what their support needs are at a university in KwaZulu-Natal. The data draws from a questionnaire administered as part of a mixed methods study on student departure. The findings indicate a myriad of support needs articulated by the students across all years of study which serves to affirm Benjamin’s theory on the complex nature of students’ lives which impacts on them. An interesting finding was students’ request for physiological support, a basic need for food. Another key finding was that of the students’ on-going need for psychological support given the stressful nature of their academic and personal challenges.